Implementasi Pengaturan Standar Perhotelan dalam Mendukung Kepariwisataan Daerah: Studi Kasus pada Ommaya Hotel di Kabupaten Sukoharjo - Hettyning, Hettyning; Khaerudin, Ariy; Dewi, Nourma (Universitas Serang Raya, 2023)
This study aims to determine the regulation of hospitality standards in supporting regional tourism and how the implementation of hospitality standards at Ommaya Hotel in supporting regional tourism in Sukoharjo Regency. The research is qualitative with a normative-empirical legal approach, using primary data and secondary data. The results of the study concluded that the regulation of hospitality standards that support tourism includes the regulation of the Tourism Business Registration Certificate (TDUP) in the field of business of providing hotel business type accommodation, the feasibility of building functions, water quality feasibility, hotel class management assessment, and tourism business certification. Ommaya Hotel has fulfilled several hotel standardizations in accordance with applicable regulations such as having a Tourism Business Registration Document (TDUP) in the field of business of providing hotel business type accommodation, water quality feasibility, hotel class classification assessment and Ommaya Hotel including two-star hotels. However, there are several hospitality standards that Ommaya Hotel does not yet have such as a certificate of the feasibility of building functions called the Certificate of Good Function (SLF), a certificate of good health, and a certificate of tourism business in the hotel sector.